Comparative study of turbulent incompressible flow past naca airfoils - Abdullah, Aslam; Roslan, Amirul Aizad; Omar, Zamri (Asian Research Publishing Network (ARPN), 2018)
The flow past the airfoils is continuously investigated in various experimental and computational aerodynamic perspectives. In this paper, a comparative study on the aerodynamic characteristics of the turbulent incompressible flow past four NACA airfoils is emphasized. Particularly, we classify these characteristics based on the basic geometries, namely symmetric and asymmetric airfoils, as well as trailing edge angles. The results confirm the general aerodynamic theory and include finding on the effect of sharp trailing edge, which complement the available airfoil datasets for improving their designs and as reference cases.